Hubungan Pengetahuan dan Sikap Ibu terhadap Pencegahan Stunting di Desa Sei Gelugur - Nurbaiti Nurbaiti; Rahmad Dani; Fahrozy Pradana Putra; Nuroida Afriani; Rs Rabiahtuddinil Adawiyah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The purpose of this study was to find out how the attitudes and knowledge of mothers related to stunting prevention in Sei Gelugur Village in 2022. In Sei Gelugur Village the correlation (relationship) method was used for research design, and mothers of children aged 6 years and over. below as a research subject. 45 people became the sample size in Sei Gelugur Village which accommodates 450 people. Results Based on the research, most (71.2%) of the research respondents' contributions to stunting prevention were included in the